The importance of modern libraries in the global information space - Aliyeva, Sahiba (Technium Social Sciences Journal, 2022)
The article describes libraries, their place and activity in the global information space. Using the experience of world libraries, the role of libraries in managing document-information flow and directions of activity were reflected in the research. As a social institution, the duties of libraries and the level of their openness to innovations in the socialized information environment are determined. The importance of the promotion of multicultural values in libraries in the informationized environment is increasing day by day. The expansion of global processes due to their scale has led to the deepening of the research field of all scientific fields, as well as social and humanitarian sciences, social philosophy and cultural studies. They include various cultural concepts, philosophical and cultural theories about the future of mankind. The development and improvement of these theories leads to an understandable explanation of the development process of the new world order. Thus, in addition to joining the social and political processes to solve the global problems of the Republic of Azerbaijan, he is worried about having a national thought and thinking, preserving the national presence, and performing the function of propaganda in order to protect libraries. and the machine in the high-level development of these currents. The course of history has come a long way from the information space to the modern one.